The Effect Of Use Of Information Technology And Human Resources Competence On The Quality Of Financial Reports At The Ministry Of Religion, Muara Enim District - Dian Astria; Linyansyah Linyansyah; Nisma Aprini (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
The purpose of this study is to find out and analyze whether the use of information technology affects the quality of financial reports at the Ministry of Religion of Muara Enim Regency and to find out and analyze whether the competence of human resources affects the quality of financial reports at the Ministry of Religion of Muara Enim Regency. The research uses a quantitative approach using SEM analysis, namely Lisrel, data collection through questionnaires, interviews to confirm research results, and documentation and data analysis. 1) The results show that the effect of Information Technology Utilization on the quality of Financial Reports is significant, and has a positive influence on the quality of Financial Reports, this means that the higher the Utilization of Information Technology, the higher the quality of Financial Reports, 2) The results show that Competence Human Resources has a significant effect on the quality of Financial Statements, this means that the research hypothesis which states that the higher the Competence of Human Resources, the higher the quality of the Financial Statements is accepted.